PENGARUH PENGGUNAAN PPENDEKATAN KONTEKSTUAL TERHADAP PENGEMBANGAN KREATIVITAS BERKARYA SENI RUPA SISWA KELAS VII SMP NEGERI 23 PADANG - Ulfa Khairani, Dr. Ramalis Hakim, M.Pd. (Universitas Negeri Padang, 2019)
This research have a purpose to develop the work creativity of “ Seni Rupa” with use contextual approach to student grade VII4 and VII8. The result of this research show that the value average which use contextual apporoach is about 81.33 and the one which use conventional method have value average about 72.90. This is show up that the creativity differences in works in the fine art. Independent influence to dependent variable that show that value t count = 4.077 and t table = 2.048 > 0.05 take positive effect to the significant off work in the fine art sector.Keyword : development, creativity, contextual approach